MORAL TREATMENT AND CONDITIONS OF SECLUSION IN THE MADHOUSE: THE LIMITS OF THE MEDICALIZATION PROCESS IN SANTIAGO, 1852 – 1891 - Torres Santibáñez, Luis (Revista de Historia Social y de las Mentalidades, 2024)
This article aims to analyze the process of medicalization of madness in Santiago during the second half of the nineteenth century. The first part contains the alienists approaches for moral treatment advocated by Chilean and foreign doctors working in the madhouse. The second part contains a description and an analysis of the conditions under which confinement was performed. It argues that psychiatric science had little impact in the way how the insane were locked in the madhouse, being displaced by philanthropic criterion. Thus, the medicalization of madness made talk to discourses of modernity with traditional discourses on the subject of how to lock up the mentally ill.